2010
DOI: 10.1016/j.jcrysgro.2010.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a-plane InN grown via MOVPE on a-plane GaN buffer layers on r-plane sapphire

Abstract: a b s t r a c tWe have performed a comprehensive investigation of the growth parameter space for the MOVPE of aplane ð1 1 2 0Þ InN on a-plane GaN buffer layers deposited on r-plane ð1 1 0 2Þ sapphire substrates. About 0:2 mm thick a-plane InN epilayers were grown on 1 mm thick a-plane GaN buffer layers in a closecoupled showerhead reactor. The growth parameters-substrate temperature, reactor pressure, V/III ratio-were systematically varied and their effect on structural, electrical, optical and morphological p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The anisotropies in a-plane InN were previously reported by Koblmuller et al [22] and Ajagunna et al [10], but in their studies, the anisotropies were negligible compared to m-plane InN and a-plane GaN. Very recently, Laskar et al [23] reported an M-shaped plot of FWHM against azimuth in plane of aplane InN, which is similar to a-plane GaN. In our MOCVD growth, these anisotropies are also significantly beyond negligible.…”
Section: Resultssupporting
confidence: 78%
“…The anisotropies in a-plane InN were previously reported by Koblmuller et al [22] and Ajagunna et al [10], but in their studies, the anisotropies were negligible compared to m-plane InN and a-plane GaN. Very recently, Laskar et al [23] reported an M-shaped plot of FWHM against azimuth in plane of aplane InN, which is similar to a-plane GaN. In our MOCVD growth, these anisotropies are also significantly beyond negligible.…”
Section: Resultssupporting
confidence: 78%
“…Trimethylgallium (TMGa), trimethylaluminium (TMAl), trimethylindium (TMIn) and ammonia (NH 3 ) were used as precursors and getter-purified nitrogen (N 2 ) as carrier gas. Details of the growth procedure can be found in our earlier optimization study [11] from where the best conditions for the growth of a-plane InN were found to be temperature T¼550 1C, pressure P¼500 Torr, and V/III characterization of the InN layers was carried out using a Philips XPERT TM HRXRD system using CuKa 1 X-rays with a hybrid monochromator providing an angular divergence of 18 arcsec in the scattering plane, and the data collected using a 2.51 open PIXcel solid state detector array. Both symmetric ð1 1 2 0Þ, ð2 2 4 0Þ reflections along c-and m-direction and the skew-symmetric ð1 0 1 0Þ, ð2 0 2 0Þ, ð3 0 3 0Þ, and ð1 0 1 1Þ were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The epitaxial growth of InN in non-polar directions is much more challenging than growth of c-plane oriented films, because the different growth mechanisms are not well understood. There are few reports of growing a-plane ð1 1 2 0Þ InN by molecular beam epitaxy [8,9] and MOVPE [10,11]. In our previous work [11] we have explored the growth parameter space for a-plane InN in a close-coupled showerhead reactor and optimized the growth conditions for a-plane InN on GaN buffer layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation